2021
DOI: 10.1051/0004-6361/202140476
|View full text |Cite
|
Sign up to set email alerts
|

How planets grow by pebble accretion

Abstract: Context. In the theory of pebble accretion, planets form by the subsequent accretion of solids (micron-sized dust and larger pebbles) and gas. The amount of nebular gas that a planet can bind is limited by its cooling rate, which is set by the opacity of its envelope. Accreting dust and pebbles contribute to the envelope opacity and, thus, influence the outcome of planet formation. Aims. Our aim is to model the size evolution and opacity contribution of solids inside planetary envelopes. We then use the result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…The delayed formation of Saturn with respect to Jupiter would be in line with the assumptions of the Grand Tack model (Walsh et al 2011), while the further delay in the formation of Uranus and Neptune would explain their lower masses in the pebble accretion paradigm (see e.g. Helled et al 2020;Brouwers et al 2021).…”
Section: Discussionmentioning
confidence: 58%
“…The delayed formation of Saturn with respect to Jupiter would be in line with the assumptions of the Grand Tack model (Walsh et al 2011), while the further delay in the formation of Uranus and Neptune would explain their lower masses in the pebble accretion paradigm (see e.g. Helled et al 2020;Brouwers et al 2021).…”
Section: Discussionmentioning
confidence: 58%
“…The dust opacity derived by Valencia et al (2013) is significantly higher than suggested by other studies (Mordasini et al 2014;Ormel 2014;Brouwers et al 2021). However, the grain opacity is expected to be high at early phases of the planetary growth when the protoplanet accretes pebbles due to efficient pebble fragmentation (Brouwers et al 2021;Chachan et al 2021), pebble ablation (e.g., Valletta & Helled 2020), and bouncing collisions between accreted pebbles (Ormel et al 2021).…”
Section: Appendix a The Importance Of Opacity And Composition Of The ...mentioning
confidence: 66%
“…As shown in previous studies, the envelope's opacity significantly affects the H-He accretion rate (e.g., Movshovitz & Podolak 2008;Mordasini et al 2014;Brouwers et al 2017Brouwers et al , 2021. The opacity that we used in this study corresponds to the sum of the gas and dust opacity.…”
Section: Appendix a The Importance Of Opacity And Composition Of The ...mentioning
confidence: 92%
“…However, it would be ideal to self-consistently compute the atmospheric metallicity, the resulting gas accretion rate, and the accompanying accretion luminosity, by taking into account the complicated interplay among solid accretion, the resulting metal enrichment of the atmosphere, the subsequent metal sedimentation, and the eventually accelerated/slowed down gas accretion. In fact, detailed calculations show that the value of f grain can be much smaller and larger than that constrained from the gas ac-10 0 10 1 10 2 10 3 10 4 10 5 10 6 10 7 Size of Solid Particles s (cm) cretion timescale (Figure 9, e.g., Movshovitz et al 2010;Ormel 2014;Ali-Dib & Thompson 2020;Brouwers et al 2021). This complexity is beyond the scope of this work and remains to be the future work.…”
Section: Caveatsmentioning
confidence: 84%